Brushless DC Motor Modeling Using Bond Graph Method and Control using LabVIEW: Speed control based calssical PID control - Alsabbagh, Ammar; Szemes, Péter Tamás; Baki, Abdulkader (Recent Innovations in Mechatronics, 2018)
This paper aims to simulate and control a three-phase Brushless DC Motor. Bond Graph method has been used to obtain fast and simple dynamic model. The system has been controlled by classical PID controller. All the paper results were fulfilled using LabVIEW program.